Differences in the clinical presentation of sleep apnea patients according to age and gender - Olli Lyyra; Aino Lammintausta; Per-Erik Gustafsson; Ulla Anttalainen; Tarja Saaresranta (PLoS ONE, 2025)
Background Data on sleep apnea is scarce in the elderly. We aimed to provide insight into the presentation of sleep apnea in people over 70 years of age including gender differences. Methods We conducted a registry study in sleep apnea patients >18 years of age diagnosed at Turku University Hospital in 2012–2019. Patients whose sleep apnea was classified at least moderate according to apnea-hypopnea index were included (N = 5870; Men = 65.7%; Mean age 57.5 ± 13.5 years). Data on cardiorespiratory polygraphy (PG) variables, Body Mass Index (BMI), pre-existing depression diagnoses, number of comorbidities, the scores of Epworth Sleepiness Scale (ESS), depression scale (DEPS) and psychological distress (12-item General Health Questionnaire, GHQ-12), and capillary blood gas results were derived from electronic medical records. Patients were stratified into three groups according to age: <70 (young-middle aged), 70–80 (elderly) and >80 years of age (very elderly). Results The severity of sleep apnea did not differ between the age groups based on any of the PG variables studied. No significant differences were found in the level of subjective daytime sleepiness between age groups. Women had higher DEPS scores than men in all age groups. Very elderly men had higher DEPS scores compared to men in other age groups (6.3 ± 4.6 vs. 5.6 ± 5.9 vs. 5.1 ± 4.8, p < 0.05) while the differences in DEPS scores did not reach significance among women. Each unit increase in SpO2 was associated with a 22% decrease in the odds of having a DEPS score of ≥9. Conclusion The severity of sleep apnea or subjective daytime sleepiness did not differ among age groups in moderate-severe sleep apnea patients. Occurrence of depressive symptoms was consistently more common in women than in men of comparable age. Mental wellbeing was the worst in the very elderly. Higher SpO2 was associated with less depressive symptoms.